A pessoa com deficiência no ensino superior: a concepção de docentes do curso de licenciatura em Educação Física de uma universidade no município de Goiânia - Mesquita, Bárbara Andressa Mendonça de Rocha (2019)
This study aims to analyze and identify the conception of Higher Education teachers regarding the access and permanence of people with disabilities in the degree course of a Faculty of Physical Education in the city of Goiânia. In this sense, our research problem arises: "What do teachers think about the access and permanence of people with disabilities in higher education?" To address this concern, we have as specific objectives: to analyze through the arguments of practical teachers prejudices and exclusion in the university context; to identify in teachers' demonstrations what pedagogical interventions are promoted by teachers to ensure the permanence of students with disabilities in the licenciatura course in Physical Education; verify in the subjects presented by the professors what are the probable actions of access and permanence carried out by the institution in the promotion of a quality education to the students with deficiency in the ESEFFEGO; to identify teachers' knowledge about inclusive education and whether teachers organize their pedagogical practice according to the educational needs of students with disabilities; to investigate how the teachers approach the corporality of the disabled people in the classes of corporal practices in the course of Physical Education and if there is some type of modification in those classes. The work was thought by the bias of the method Materialism Dialectic Historique with quantiqualitative approach to analyze the data researched. The chosen place for the studies was a degree course in Physical Education in Goiânia, the technique of data collection used was a semistructured interview, applied to 12 teachers from three different areas: human, biological and teachers of the disciplines of corporal practices that already have been teaching or are teaching one of the compulsory subjects for disabled academics. The results show that, in the conception of university professors, the University took some actions to ensure the access and permanence of these students, among them the legal reserve of vacancies for people with disabilities bythe quota system, the creation of the Access Learning Center without Limits (NAASLU) and the hiring of support teachers. Despite these actions, the teachers point out changes in attitudes that can be made to effective inclusion practices in ESEFFEGO, such as the accomplishment of structural, pedagogical, curricular, attitudinal and technological adaptations in the Physical Education course, as they believe that such actions aim students with disabilities in the educational context. Thus, it is possible to conclude from the university teachers' conception that they still reproduce prejudicial practices based on a university based on the instrumental and competitive rationality in which some teachers base their pedagogical practice. However, in order to ensure the adequate access and permanence of persons with disabilities in higher education, the University needs to fulfill its social function through the collaboration of the agents involved in the pedagogical process of students with disabilities, among them academic management, teachers, teachers students, family members of students with disabilities and if possible multidisciplinary assistance, in order to build an educational institution that adds in its daily academic principles the principles of inclusive education, which seek to strengthen respect for bodily diversity.